موقف الحركة الوطنية الجزائرية من الإنزال الأنجلوا – أمريكي بسواحل الجزائر (6-9 ) نوفمبر 1942 - زروقي, محمد (Université de M'sila, 2018)
ملخص باللغة العربية : كانت الجزائر عشية الحرب العالمية الثانية هدفا لدعاية متضاربة بين دول الحلفاء ( بريطانيا – الولايات المتحدة الامريكية ) و دول المحور( ألمانيا – إيطاليا) و ذلك سعيا منهما لكسب تأييد الشعب الجزائري و التأثير عليه لجعله مسخرا لخدمة مصالحهم, فاتخذا من وسائل الإعلام وسيلة لإيصال رسائلهم مثل المحطات الإذاعية(راديو برلين ) , الجرائد و المجلات . و مع نزول قوات الحلفاء بالجزائر (6-9) نوفمبر 1942 في كل من الجزائر العاصمة ووهران و سيطرتهم عليها بدأ ت مظاهر إنبعاث في نشاط الحركة الوطنية الجزائرية , وتبلورت مواقف متباينة بين المؤيد( الحزب الشيوعي الجزائري – فدرالية المنتخبين المسلمين الجزائريين ) و المعارض( حزب الشعب الجزائري – جمعية العلماء المسلمين الجزائريين – الشعب الجزئري ) لتواجد قوات الحلفاء بالجزائر .و كان لتباين المواقف الأثر الكبير في التحولات التي ستعرفها الحركة الوطنية الجزائرية بعد عملية الإنزال , من خلال تواصل فرحات عباس مع ممثل الحلفاء دون جدوى , مما إضطره للتقارب مع مختلف إتجاهات الحركة الوطنية الجزائرية سعيا منه لتوحيد الصف , فتبلور الفكر التحرري من خلال بيان 3 فيفري 1943 م ,فكان الرد الفرنسي السلبي من البيان وإصداره لأمرية 07 مارس 1944 م المتعلقة بوضعية الفرنسيين المسلمين في الجزائر بعيدا عن امال و طموحات الشعب الجزائري , ولم يأخذ بعين الإعتبار مقترحات ممثلي و أقطاب الحركة الوطنية الجزائرية , فاعتبره القادة الوطنيون عبارة عن مماطلة لأنه كان دون المطالب المقدمة في البيان و ملحقه , و موجها لطبقة معينة مرتبطة مصلحيا بفرنسا, فكان الرد عليه بتأسيس حركة أحباب البيان و الحريات 14 مارس 1944 بقيادة فرحات عباس التي تبين من خلالها فيما بعد مدى الاختلاف في التوجهات السياسية و اهداف الكفاح ضد المستعمر. Absract : Algeria was the eve of the second world war a goal conflicting propaganda among the allied powers (Britain-United States) and the axis powers (Germany-Italy) and in an effort to gain the support of the Algerian people and influence him to make him stretching to serve their interests, taken from media means to deliver their messages such as radio stations (radio Berlin), newspapers and magazines. And with the descent of the Allied forces in Algeria (6-9) November 1942 in all of Algeria's capital, Oran and their control has started the emission aspects in the activity of the Algerian national movement, and crystallized different positions among Pro (Algerian Communist Party-elected Federal Algerian Muslims) and exhibitions (Algerian people's Party – Association of Algerian Muslim scholars – the Algerian people) for the presence of allied forces in Algeria, and had a significant impact on attitudes contrast shifts that will recognize the Algerian national movement after Geoghegan , Through contact with Ferhat Abbas allies to no avail, forcing him to approach the different trends of the Algerian national movement seeking to unite, libertarian thought evolved through a statement.3 February 1943, the French response was negative statement and issuing prescriptive 07 March 1944 on the status of French Muslims in Algeria, away from the hopes and aspirations of the people of Algeria, and did not take into account the proposals of the representatives and the Algerian national movement of electrodes, considered national leaders are stalling because it was without the demands in the statement and inserts, and directed to a specific layer associated with belkhadim France , Was answered by lovers of movement and the freedom 14March1944 led by Ferhat Abbas which show later how different political orientations and objectives of the fight against the colonizers.
Keywords: الكلمات المفتاحية : الإنزال الأنجلو- أمريكي – الحركة الوطنية الجزائرية– بيان فيفري 1943- المواقف المؤيدة للإنزال . Keywords : Anglo-American landing – the Algerian national movement – statement of February 1943- attitudes for landing.